Revisiting pollen-pistil interaction and cross incompatibility in maize - Husna Nugrahapraja; Edoardo Bertolini; Mario Enrico Pe (Institut Teknologi Bandung, 2019)
The review addressed aspects of plant fertilisation and the phenomenon of genetic cross-incompatibility in maize controlled by the Gametophyte1 locus. This phenomenon determines the failure to accomplish successful fertilisation and a full seed set when pollen grains carrying the ga1 allele pollinate female inflorescences carrying the Ga1-strong (Ga-1s) allele in the homozygous state (Ga1-s/Ga1-s). We divided the review work into several topics — first, the introduction of sexual plant reproduction. Second, pollen-pistil interactions in plants. Third, reproductive barriers during plant reproduction. Third, Incompatibility in plants. Fourth, fine mapping of the Ga1 locus in maize. Fifth, recent researches on Ga1-related cross-incompatibility in maize.